A bottom-up approach to techno-economic assessment of harnessing tidal energy in European coastal zones (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The increasing scarcity of onshore land and the rising efficiency and competitiveness of marine renewable energies (MRE) are accelerating the offshore energy transition. However, the limited experience of commercial MRE deployments and the scarcity of detailed cost data availability often lead to unrepresentative economic models. This paper proposes a cost model based on the bottom-up approach to three tidal energy converters (TECs): monopile, floating, and gravity-based substructure (GBS), combined with a power assessment based on the available tidal current models. Cost functions for multiple TEC components, available in the tidal industry literature, were fitted. The techno-economic evaluation was performed at four marine locations: Fall of Warness (Scotland), Punta Pezzo (Italy), Fromveur, and Raz Blanchard (France). Due to their proximity to the sea surface, monopile and floating TECs achieve the highest annual power output and capacity factor at Fromveur, equal to 393 kW and 39.35 %, respectively. In all cases, an asymptotic decreasing trend in LCoE is observed as the installed capacity of the sites increases, with LCoE ranging between 329 and 50 €/MWh with 32 turbines installed. Among all the sites analyzed, Fall of Warness and Punta Pezzo generated the lowest and highest LCoE values, respectively. In all case studies, except for Punta Pezzo, monopile TECs generated the lowest LCoE values, followed by floating type. At Punta Pezzo, floating TEC proved more cost-effective due to greater water depth (100 m), explaining how monopile is preferable in shallow waters (